A dynamic version of the super-replication theorem under proportional transaction costs. Issue 1 (2nd January 2023) - Biagini, Francesca; Reitsam, Thomas
Abstract: We extend the super-replication theorem in a dynamic setting, both in the numéraire-based as well as in the numéraire-free setting. For this purpose, we generalize the notion of admissible strategies. In particular, we obtain a well-defined super-replication price process, which is right-continuous under some regularity assumptions.